Religiosity, Secularity and Pluralism in the Global East - Song, Francis Jae-ryong (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This special issue includes 11 articles from the Inaugural Conference of the East Asian Society for the Scientific Study of Religion. It offers theoretical and methodological reflections, and covers various religions in different East Asian societies and diasporic communities.